A Rare Anatomical Variation of the Spinal Accessory: Case Report - Abdullah Al-Shaharani (Journal of Umm Al-Qura University for Medical Science, 2021)
Anatomical variation in the location of the spinal accessory nerve as it relates to the internal jugular vein has been reported in the literature and anatomy texts. Knowledge of the landmarks of the spinal accessory nerve and its relationship to the internal jugular vein is extremely helpful in its identification during neck surgery for precluding neurovascular complications. The nerve mostly passes laterally (anterior) or medially (posterior) to the internal jugular vein at the level of the medial aspect of the posterior belly of the digastric muscle. However, there is a rare anatomical and surgical variant. In our case report, we describe an unusual relationship of the spinal accessory nerve to the internal jugular vein. In our case study, the nerve pierces the internal jugular vein.